Sacralisation of the social space: A study of the trans-border expansion of the redemption camp of the Redeemed Christian Church of God - Adedibu, Babatunde A. (HTS Teologiese Studies / Theological Studies, 2019)
Urban cities in the sub-Saharan Africa have witnessed unprecedented transformation because of the proliferation of religious orders within the social landscape. From Nigeria, Ghana and Cameroon to Uganda, religious practitioners are actively involved in the spatial transformation through the construction of sacred spaces or prayer camps. The Redeemed Christian Church of God (RCCG) typifies one of the several examples of African Pentecostal denominations with transnational status in 200 countries across the world with the hub of its international office situated at the Redemption Camp, Mowe, Nigeria. The sacralisation of forest areas spanning 1600 ha of land has redefined religious institutions such as RCCG as perhaps one of the largest owners of private estate in Nigeria. However, there seems to be an intentional replication of the Redemption Camp, Mowe across Nigeria as well as across the Atlantic as part of the RCCG missionary enterprise. This study aims to utilise the ethnography of the Redemption Camps in Nigeria and Floyd, Texas, United States. The theoretical framework of social worlds is employed to examine the dynamics of religious creativity, innovations, contextual challenges of place-making involved in creating Redemption Camps across borders by the leadership of RCCG through the appropriation of religious capital of its community of sentiments.
Free
Keywords: Nigeria; Placemaking; Redeemed Christian Church of God; Redemption Camp; Sacralisation; United States; religion